Education on Making Dishwashing Liquid Soap and Ecoprint Pounding for the Empowerment of PCM and PCNA Cadres in Kebakkramat - Siti Fatimah; Ahmad M. Fuadi; Akida Mulyaningtyas; Kun Harismah; Dedi Gunawan (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The Muhammadiyah Branch Management (PCM) and Nasyiatul 'Aisyiyah Branch Management (PCNA) of Kebakkramat are organizations that are active in social, religious, and cadre development activities in Karanganyar. The challenges of regeneration and strengthening cadre activities have driven the need for practical and relevant empowerment programs. These community service activities are carried out through creative economy training in the form of making liquid dish soap and ecoprinting as an effort to improve the skills and capacity of cadres. Liquid soap was chosen because it is a household necessity with broad business opportunities, while ecoprinting was chosen as an environmentally friendly craft skill that can be developed into products of artistic and economic value. The implementation methods included introduction, education, implementation, evaluation, and monitoring. The results of the activities showed an increase in the creativity and understanding of cadres in utilizing business opportunities based on practical skills. This activity also contributed to strengthening the association's independence and competitiveness and produced outputs in the form of scientific publications, documentation products, and potential intellectual property rights (IPR). This program is expected to be a strategic step in strengthening cadre capacity and supporting sustainable community empowerment.